Kematangan emosi dan burnout pada guru: Bagaimana peran strategi coping sebagai variabel intervening? - Damayanti, Pramesti Ardelia; Nainggolan, Eben Ezer; Muslikah, Etik Darul (INNER: Journal of Psychological Research, 2023)
Abstract Burnout is an emotional state in individuals that are experienced in all jobs if they get work pressure. One of the personality factors that trigger burnout is the ability to control emotions. Individuals who have patience and can control their emotions show signs of emotional maturity. To prevent burnout, it is necessary to develop problem-solving strategies for the problems being experienced, namely coping strategies. This study aims to determine whether coping strategies as intervening variables can influence the relationship between emotional maturity and burnout. The sample of this research is teachers in Surabaya. Sampling was carried out using a simple random sampling method. Data analysis used Path Analysis (a combined model between multiple regression models and mediation models). The results showed 1) there is a significant influence between emotional maturity and burnout, 2) emotional maturity and burnout have no significant effect on coping strategies 4) coping strategies mediate emotional maturity through burnout. Keywords: Coping Strategies; Emotional Maturity; Burnout